An intervention to increase physical activity in children: A randomized controlled trial with 4-year-olds in preschools - Pate, R.; Brown, W.; Pfeiffer, K.; Howie, Erin; Saunders, R.; Addy, C.; Dowda, M. (2016)
Â© 2016 American Journal of Preventive Medicine. Introduction A majority of preschool-aged children spend a significant portion of every weekday in a preschool or child care setting, where they typically participate in limited physical activity. This study determined if an ecologic physical activity intervention in preschools increases children's moderate- to vigorous-intensity physical activity (MVPA). Design RCT, with preschool as the unit of randomization and analysis. Child physical activity was measured by accelerometry. Mixed model analysis of covariance with preschool as a random variable was used to test the effects of the intervention on physical activity in the total group and in sex-specific subgroups. Data were collected in 2008-2010 and analyzed in 2012-2014. Setting/participants Children in 4-year-olds' classrooms in 16 preschools, pair matched and assigned to intervention or control groups. Intervention The intervention focused on increasing children's physical activity by changing instructional practices. Researchers trained preschool teachers to engage children in physical activity during (1) structured, teacher-led physical activity opportunities in the classroom; (2) structured and unstructured physical activity opportunities at recess; and (3) physical activity integrated into pre-academic lessons. Research staff encouraged teachers to adapt the intervention to their classrooms. Main outcome measures Minutes/hour of MVPA during the preschool day. Results In an analytic sample of 379 children (188 intervention, 191 control), those in the intervention schools engaged in significantly more MVPA than children in control schools (7.4 and 6.6 minutes/hour, respectively). This difference remained significant after adjusting for parent education and length of the school day (half versus full day). In the sex-specific analyses, the difference was significant for girls (6.8 vs 6.1 minutes/hour of MVPA, respectively) but not for boys (7.9 vs 7.2 minutes/hour, respectively). Conclusions A flexible ecologic physical activity intervention that trains teachers to provide children with opportunities to be active throughout the school day increased MVPA in preschool children.